Simulation analysis of cycle skipping strategy in SI engine fueled with ethanol gasoline mixture - Gürbüz, Dr. Hüseyin (Murat CİNİVİZ, 2023)
Researches are carried out with different methods to reduce the emissions emitted by conventional fuel engines. In addition to using alternative fuels, especially ethanol, in gasoline engines, fuel injection, and combustion controls are applied in various strategies. In this study, the effects of various cycle skipping strategies on emissions were analyzed through a numerical model of a single-cylinder naturally aspirated spark ignition (SI) engine. The validated model was fueled with an ethanol gasoline blend with 30% ethanol content. The model engine was operated at partial load and 1500 rpm constant engine speed under Normal (N), 1N1S, 2N1S and 3N1S cycle skip strategies. NOx emission increased with all strategies due to increased in-cylinder temperature with more fuel depletion in ignition cycles. The BSFC decreased by 9.93%, 13.67% and 5.93% in the 1N1S, 2N1S and 3N1S cycle skipping strategies, respectively. CO and HC emissions decreased with all cycle skipping strategies compared to the normal cycle.
Keywords: Mechanical Engineering; Makine Mühendisliği